Frequency of intraoperative cardiac arrest and medium-term survival - Sebbag, Ilana; Carmona, Maria José Carvalho; Gonzalez, Maria Margarita Castro; Alcântara, Hermes Marcel; Lelis, Rolison Gustavo Bravo; Toledo, Flavia de Oliveira; Aranha, Gustavo Fábio; Nuzzi, Rafael Ximenes do Prado; Auler Júnior, José Otávio Costa (São Paulo Medical Journal, 2013)
CONTEXT AND OBJECTIVE: Although advances in surgical and anesthetic techniques have reduced perioperative morbidity-mortality, the survival rate following cardiac arrest remains low. The aim of this study was to evaluate, over the course of one year, the prevalence of intraoperative cardiac arrest and the 30-day survival rate after this event in a tertiary teaching hospital. DESIGN AND SETTING: Prospective cohort study in a tertiary teaching hospital. METHODS: Following approval by the institutional ethics committee, anesthetic procedures and cases of intraoperative cardiac arrest between January and December 2007 were evaluated. Patients undergoing cardiac surgery were excluded. The data were gathered prospectively using the modified Utstein model, with evaluation of demographic data, pre-arrest conditions, intraoperative care, care during arrest and postoperative outcome up to the 30th day. The data were recorded by the attending anesthesiologist. RESULTS: During the study period, 40,379 anesthetic procedures were performed, and 52 cases of intraoperative cardiac arrest occurred (frequency of 13:10,000). Among these, 69% presented spontaneous return of circulation after the initial arrest, and only 25% survived for 30 days after the event. The following factors were associated with shorter survival: American Society of Anesthesiologists physical status IV and V, emergency surgery, hemorrhagic events, hypovolemia as the cause of arrest and use of atropine during resuscitation. CONCLUSIONS: Although the frequency of cardiac arrest in the surgical environment has declined and resources to attend to this exist, the survival rate is low. Factors associated with worst prognosis are more frequent in critical patients.